High antibody levels and reduced cellular response in children up to one year after SARS-CoV-2 infection - Eva-Maria Jacobsen; Dorit Fabricius; Magdalena Class; Fernando Topfstedt; Raquel Lorenzetti; Iga Janowska; Franziska Schmidt; Julian Staniek; Maria Zernickel; Thomas Stamminger; Andrea N. Dietz; Angela Zellmer; et al. (Nature Communications, 2022)
Severity of SARS-CoV-2 infection is different in adults and children which involves the immune response. Here using a parent and children cohort with 4 month and 12 month sampling times, the authors show enhanced levels and increased breadth of anti-spike antibody level over time but reduced specific T cell and B cell numbers in children.